Novel and Simple Nomograms Using Inflammation and Nutritional Biomarkers for Stage II–III Colon Cancer, Taking "Time after Curative Surgery" into Consideration. (25th July 2022) - Mazaki, Junichi; Katsumata, Kenji; Tago, Tomoya; Kasahara, Kenta; Enomoto, Masanobu; Ishizaki, Tetsuo; Nagakawa, Yuichi; Tsuchida, Akihiko
Abstract: Purpose: Recurrence of colon cancer is associated with time after curative surgery. This study aimed to construct novel nomograms to predict relapse-free survival (RFS) in stage II–III colon cancer, considering "time after surgery" and using various inflammatory and nutritional biomarkers. Methods: All 542 patients who underwent radical surgery for stage II–III colon cancer between January 2000 and August 2015 at our institute were retrospectively analyzed. Time-dependent receiver operating characteristic curves and cutoff values were obtained for neutrophil-lymphocyte ratio (NLR), lymphocyte-monocyte ratio, platelet-lymphocyte ratio, Japanese modified Glasgow prognostic score (mGPS), C-reactive protein-albumin ratio (CAR), prognostic nutritional index, and controlling nutritional status (CONUT) for each postoperative period (1 − 5 years). We used Cox proportional hazard analyses to evaluate independent risk factors and to construct nomograms in each period. Results: We obtained a good accuracy in NLR, CAR, mGPS, and CONUT (area under the curve > 0.5). NLR was the only preoperative independent risk factor, except age, in multivariate analysis. We constructed the nomograms and obtained a good discrimination value of the concordance index in each period (>0.75). Conclusion: Using inflammatory and nutritional biomarkers, we established and calibrated novel nomograms for predicting time-dependent RFS for stage II–III colon cancer patients.